Concentrating of Pineapple Cannery Liquid Waste by Ultrafiltration and Reverse Osmisis System - Chalongsri Warnitchakorn (Chulalongkorn University, 2014)
Thesis (M.Sc.)--Chulalongkorn University, 1982